Morphomolecular charecterisation of the variants of piper nigrum L. variety panniyur -1 - Smitha Bhasi (Department of Plant Biotechnology, College of Agriculture, 2008)
The study entitled “Morphomolecular characterization of variants of Piper nigrum L. variety Panniyur-1” was conducted at the Department of Plant Biotechnology, College of Agriculture, Vellayani, Thiruvananthapuram and in the Block V of Panniyur-1 at the Regional Agricultural Research Station (RARS), Ambalavayal during the year 2006-2007 with an objective of characterizing the variants of black pepper variety Panniyur-1 based on morphological traits and RAPD profiles.